2009
DOI: 10.1371/journal.pone.0004632
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Environmental Mechanical Stress Controls Tumor Spheroid Size and Morphology by Suppressing Proliferation and Inducing Apoptosis in Cancer Cells

Abstract: BackgroundCompressive mechanical stress produced during growth in a confining matrix limits the size of tumor spheroids, but little is known about the dynamics of stress accumulation, how the stress affects cancer cell phenotype, or the molecular pathways involved.Methodology/Principal FindingsWe co-embedded single cancer cells with fluorescent micro-beads in agarose gels and, using confocal microscopy, recorded the 3D distribution of micro-beads surrounding growing spheroids. The change in micro-bead density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
405
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(449 citation statements)
references
References 28 publications
41
405
3
Order By: Relevance
“…Once the space is filled near the origin of TECs, TECs begin to feel a reciprocal tissue resistance force from the surrounding stromal tissue and tend to grow in the longitudinal direction, i.e., in the direction of less stress. This is qualitatively consistent with experimental results described earlier on anisotropic growth (Helmlinger et al 1997;Cheng et al 2009). Figure 20(H) shows the time course of the tumor population for both cases in (F) and (G) above.…”
Section: The Effect Of the Stiffness Of The Stromal Tissuesupporting
confidence: 90%
See 1 more Smart Citation
“…Once the space is filled near the origin of TECs, TECs begin to feel a reciprocal tissue resistance force from the surrounding stromal tissue and tend to grow in the longitudinal direction, i.e., in the direction of less stress. This is qualitatively consistent with experimental results described earlier on anisotropic growth (Helmlinger et al 1997;Cheng et al 2009). Figure 20(H) shows the time course of the tumor population for both cases in (F) and (G) above.…”
Section: The Effect Of the Stiffness Of The Stromal Tissuesupporting
confidence: 90%
“…Parameter PRCC\ k Parameter PRCC\ k other tumor types that the surrounding medium affects growth of tumor spheroids (Helmlinger et al 1997;Cheng et al 2009). Transformed mammary epithelial cells may also respond to stresses by increasing FGF and VEGF signaling to promote their proliferation and by increasing production of MMPs to promote invasion (Paszek and Weaver 2004).…”
Section: The Mathematical Model For Tumor Growth In a Ductmentioning
confidence: 99%
“…Indeed, embryonic morphogenesis proceeds mostly by rearrangements within limited cell assemblies 2 that are, for instance, related to domains of gene expression 3 . However, the collective behaviour of well-defined cell groups is also involved in other situations such as the response of cancer cell assemblies to compression 4,5 or the adaptation and evolution of tumours that have been proposed to be described by very generic processes 6 . On a different note, high-density newgeneration cell chips operate at these mesoscales to analyse populations of a few hundred cells 7 , and tissue engineering strategies now aim at a very accurate spatial relative and absolute positioning of groups of cells of different types 8 .…”
mentioning
confidence: 99%
“…Helmlinger et al [11] set up an experiment where cells were grown in an elastic gel and they found that the growth of the tumor was gradually stalled (reaching compressive stresses of several kPa) although no indication of apoptosis was reported. In similar experiments, however, Cheng et al [12] concluded induced apoptosis in regions of high compressive stress and allowing proliferation in regions of low stress. Basan et al [13] studied the influence of mechanical stress by compressing tissue in a cylindrical chamber.…”
Section: Introductionmentioning
confidence: 93%